Direct measurement of enthalpy and entropy changes in NH3 promoted O2 activation over Cu−CHA at low temperature. Issue 11 (3rd May 2021) - Wang, Xueting; Chen, Lin; Vennestrøm, Peter N. R.; Janssens, Ton V. W.; Jansson, Jonas; Grönbeck, Henrik; Skoglundh, Magnus
Abstract: Oxygen activation is a key step in the selective catalytic reduction of nitrogen oxides with ammonia (NH3 ‐SCR) over Cu‐chabazite. We present direct measurements of oxygen adsorption at low temperatures over [NH3 −Cu−NH3 ] + complexes and framework‐bound Cu + species in Cu‐chabazite with Si/Al=14 using isothermal microcalorimetry combined with mass spectrometry. The enthalpy change for O2 adsorption over [NH3 −Cu−NH3 ] + complexes at 200 °C is determined to be −79 kJ/mol. By fitting a Langmuir isotherm, the corresponding entropy change is determined to be −142 J/(mol*K) at 10 % O2 . The results show that O2 adsorption at low temperatures over [NH3 −Cu−NH3 ] + complexes is more facile than on framework‐bound Cu + species. The experimental results are in agreement with density functional theory calculations showing a lower barrier for O2 activation over the [NH3 −Cu−NH3 ] + complexes as compared to the framework‐bound Cu + species. Abstract : The heat release of oxygen adsorption on a pair of [NH3 −Cu−NH3 ] + complex in Cu−CHA is recorded using micro calorimetry combined with mass spectrometry. The apparent activation energy, as well as enthalpy and entropy changes of this process are determined experimentally.